Changes in the Public Spaces at the Collective Living Quarters in Hanoi: A Case Study of Thanh Cong Living Quarter - Duong Tat Thanh (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The collective living quarters, referred to as ‘khu tập thể’ in Vietnamese, a familiar phrase used by Hanoians, is connected with periods of subsidy and is an unforgettable memory that is part of the lives of many families, who were officers and civil servants working in the State sector. Thanh Cong quarter is one of the most prominent areas in Hanoi with upgraded design, constructions, and landscape compared to other collective living quarters in the city. It is seen as a completed living area offering a fully functioning lifestyle for its community. Thanh Cong quarter underwent a lot of changes under the transition to a socialist oriented economy in Vietnam in the late 1980s. The original design of the collective living quarters was not suitable for private businesses, which led to the encroachment on public spaces. As a result, the quarter could not avoid impacts on the appearances and daily routines of residents. Step-by-step changes were a common phenomenon within all collective living quarters from this period. Received 15th June 2024; Revised 5th September 2024; Accepted 5th October 2024